2018
DOI: 10.5713/ajas.17.0058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supplemental canola or soybean oil on milk yield, fatty acid profile and postpartum weight changes in grazing dairy goats

Abstract: ObjectiveThis experiment was designed to evaluate the effect of supplementation with soybean or canola oil on milk production and the composition of long chain fatty acids as well as weight changes in the goats and their kids.MethodsThirty nine mulitparous crossed Alpine×Nubian goats (initial body weight [BW] 43.5±1.7 kg) from the day of parturition were assigned to the treatments: grazing control (n = 15); grazing plus 20 mL/goat/d of supplemental soybean oil (n = 12); and grazing plus 20 mL/goat/d of supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(38 reference statements)
1
8
0
1
Order By: Relevance
“…At all events, the current results supported that addition of oils as a source of energy could improve basically balance of feedstuffs which achieved goodness in productive performance recovery in dairy goats. The observed consequences are in confirmed with findings obtained on dairy goats received different oils as sunflower oil , linseed and sunflower oil (Khalifa et al, 2016), rapeseed oil (Eknaes et al, 2017), grapes seed oil (Muktiani et al, 2018), and soybean oil (Lerma-Reyes et al, 2018). Price of sell kg of goat milk is 3.25 (EGP), Price in year 2016 for CFM, BH and RS were 3200, 750, 350 EGP /ton and linseed and sunflower 25 and 11 EGP / kg, respectively, **Economic efficiency (%) = money out put (price of sell milk) ÷ money input (total price of feed consumed) ×100, *** EE (%) relative to control with G2 or G3= EE amount of G2 or G3 -EE amount of G1÷ EE amount of G1×100 +100 (conceder EE of G1 is 100%).…”
Section: Economic Efficiencysupporting
confidence: 87%
See 2 more Smart Citations
“…At all events, the current results supported that addition of oils as a source of energy could improve basically balance of feedstuffs which achieved goodness in productive performance recovery in dairy goats. The observed consequences are in confirmed with findings obtained on dairy goats received different oils as sunflower oil , linseed and sunflower oil (Khalifa et al, 2016), rapeseed oil (Eknaes et al, 2017), grapes seed oil (Muktiani et al, 2018), and soybean oil (Lerma-Reyes et al, 2018). Price of sell kg of goat milk is 3.25 (EGP), Price in year 2016 for CFM, BH and RS were 3200, 750, 350 EGP /ton and linseed and sunflower 25 and 11 EGP / kg, respectively, **Economic efficiency (%) = money out put (price of sell milk) ÷ money input (total price of feed consumed) ×100, *** EE (%) relative to control with G2 or G3= EE amount of G2 or G3 -EE amount of G1÷ EE amount of G1×100 +100 (conceder EE of G1 is 100%).…”
Section: Economic Efficiencysupporting
confidence: 87%
“…Enhancing milk amount with oil consumption in G2 and G3 attributed to high α-linolenic acid (ALA) in rations were able to upregulate the peroxisome proliferatoractivated receptors (PPAR-α) gene and downregulate the stearoyl-CoA-desaturase gene compared to control diets with low ALA content (Trabalza-Marinucci et al, 2016). According to Lerma-Reyes et al (2018), they found that oil supplementation could prevent the negative energy balance which has amelioration changes in milk production, then changes in milk production have been observed with higher levels of lipids in diets.…”
Section: Offspring Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the higher secretion of C18:1n9t and 18:1n9c with soybean oil could be due to partial biohydrogenation of dietary cis-9 C18:1 to C18:0 followed by its desaturation by stearoyl-CoA desaturase and due to partial protection of soybean oil cis-9 C18:1 from ruminal biohydrogenation [ 44 ]. Tannin-containing diets reduce ruminal biohydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, as demonstrated in many studies [36][37][38], fat supplementation rich in PUFA (linseed, sunflower and fish oils) decrease de novo synthesis of C4:0-C15:0 in the mammary gland, which is in opposite to results obtained in the present study. During the transition period, ruminants normally mobilize extensively triglycerides from their body fat reservers, mainly in the form of C16:0, C18:0, and C18:1 cis-9 [39]. Such high uptake of these fatty acids by mammary gland tissue inhibits de novo synthesis of short chain fatty acids.…”
Section: Fatty Acids Profile In Colostrummentioning
confidence: 99%